Clinical effects and safety of different transarterial chemoembolization methods for bridging and palliative treatments in hepatocellular carcinoma - Mohr, Isabelle; Vogeler, Marie; Pfeiffenberger, Jan; Sprengel, Simon David; Klauß, Miriam; Radeleff, Boris; Teufel, Andreas; Chang, De-Hua; Springfeld, Christoph; Longerich, Thomas; Merle, Uta; Mehrabi, Arianeb; et al. (Journal of cancer research and clinical oncology, 2022)
Purpose: We assessed and compared clinical effects and safety endpoints of three methods of transarterial chemoembolization (TACE), conventional (cTACE), with drug-eluting beads (DEB-TACE), and with degradable starch microspheres (DSM-TACE), used in patients with hepatocellular carcinoma (HCC) in the bridging to liver transplant (LT) and the palliative setting. Methods: In our center, 148 patients with HCC underwent 492 completed TACE procedures between 2008 and 2017 (158 for bridging to LT; 334 for palliative treatment) which we analyzed retrospectively. Of these procedures, 348 were DEB-TACE, 60 cTACE, and 84 DSM-TACE. Results: The cTACE procedure revealed a significantly longer period of hospitalization (p = 0.02), increased occurrence of nausea (p = 0.025), and rise in alanine transaminase (ALT) levels (p = 0.001), especially in the palliative setting. In the bridging to LT cohort, these clinical endpoints did not reach statistical significance. Conclusions: The clinical safety of different TACE methods for HCC in both the palliative and the bridging to LT setting was equivalent. In the palliative setting, the cTACE procedure revealed an increased risk for adverse clinical effects such as nausea, elevation of ALT, and a prolonged period of hospitalization what might either be related to the systemic effects of the chemotherapeutic agent or to the differences in both collectives. Thus, further studies must be conducted on a larger number of TACE procedures to effectively explore the clinical side effects of the various TACE variants.